PENGARUH ASPEK KEUANGAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Permata Sari, Risky Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
Financial aspects of the company is a reflection of a companys value, which if both the financial aspects of the company also tend to have better survival. Going concern opinion is that given the auditors opinion on the company so the company nor the investors can see how the companys survival in the future. Going concern opinion beneficial to many parties, for the companys internal and external. The high rank of financial ratios such as return on assets (ROA), Debt to Asset Ratio (DAR), Liquidity, size of company that can be seen from the sales companies each year are some of the factors that can influence financial aspects going concern audit opinion. Samples were company listed on the Indonesia Stock Exchange in 2010-2013, amounting to 13 companies per year by using purposive sampling technique. The technique of collecting data is documentation. This type of research uses quantitative data annual reports companies listed in Indonesia Stock Exchange. Analysis using logistic regression analysis. The results showed that the ROA and Sales significant effect on the going concern audit opinion while the value of DAR and Liquidity does not affect the going concern audit opinion. Desirable for future research to extend the study to increase the sample of all companies listed on the Indonesia Stock Exchange, adding a longer period of study and add to other factors that might impact on going-concern audit opinion.